Konceptualna zasnova sistema za katalogizacijo na osnovi IFLA Library Reference Model (LRM) - Pauman Budanović, Mihela (Knjižnica, 2022)
Purpose: The purpose of the research was the design of a prototype cataloguing system, which provides easier bibliographic data entry, is based on the advantages of the IFLA LRM model and follows cataloguers’ thought process.Methodology/approach: Prior to the conceptual design of the new cataloguing system, we have conducted five qualitative studies for a comprehensive understanding of the cataloguers’ thought processes in different contexts. A total of 119 Slovenian cataloguers from 11 libraries took part in the studies conducted between May 2014 and May 2019. Various methodological approaches have been used for data gathering, such as: observation, thinkaloud protocol, screen recording, concept mapping, focus group, and “Wizard of Oz” method. Results: The proposed prototype presents a possible approach towards more efficient bibliographic data entry and a cataloguing process resulting in less duplicate work and repetition and shows how a LRMbased cataloguing module could improve the existing cataloguing process.Research limitation: The research was limited only to works of fiction and descriptive cataloguing. Additionally, only the basic set of LRM entities was implemented.Originality/practical implications: Our research could serve as a basis for the future development of COBISS cataloguing software, when we switch to the new cataloguing paradigm in Slovenia. The prototype could also be considered as an illustrative training tool to familiarize cataloguers with LRM.
Keywords: bibliotekarstvo; cataloguers; cataloguing process; IFLA Library Reference Model (LRM); katalogizacija; katalogizatorji; knjižnični katalogi; library catalogues; mental processes; miselni procesi